Atypical sebaceous cyst: uncommon and unusual locations - Mukherjee, Sudeb; Datta, Pramathanath; Datta, Suhana (International Surgery Journal, 2016)
Sebaceous cysts are common in day to day practice. But unusual locations with atypical presentations may pose problem in diagnosis as well as management. Here we have reported 4 cases of such atypicality which are very uncommon and unusual.